Phenomena of Identity Politics in Indonesia: Interaction Analysis between Religion and Ethnicity in West Sumatera - Ibrahim, Risnaldi; Yusoff, Mohammad Agus; Asrinaldi, Asrinaldi; Pinto, Julio Tomas; Irayanti, Irma (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
In 2024 Indonesia will again hold General Elections. This national political succession has become a magnet for all Indonesian people to talk about it in conversations in various public spaces. Interestingly, the public discussion of each candidate who advances in the general election is inseparable from the religious and ethnic background that will determine the people's choice of a candidate. The problem that arises is that religious and ethnic issues tend to cause hostility among potential supporters. This study aims to analyze how identity politics, especially religion and ethnicity, influences people's choice of a candidate. This research uses qualitative methods with phenomenological and ethnographic approaches. Sources of data are taken from various communication theories, mass psychology, political communication theory, and results of analysis of various previous research results that examine these issues and problems in different contexts and issues. All the findings in this study will be discussed in an interesting way and based on phenomena that occur in society.